Artificial Intelligence Imaging to Observe the Protective Effect of Hydrogen Sulfide on Acute Kidney Injury Caused by Urinary Sepsis. (25th November 2021) - Yu, Ziying; Zhang, Xiaoli
Abstract : With the development of medical technology products and the rapid development of computer technology, medical AI has become a hotbed in scientific research and clinical practice. Some medical AI-assisted diagnosis has been applied to the clinic to assist doctors in formulating treatment plans. The traditional method of clinical diagnosis and treatment is that the physician makes an intentional diagnosis and then performs ancillary tests. The clinician performs diagnosis and treatment by identifying clinical symptoms and analyzing auxiliary examination results. Modern medical AI is based on big data collection and analyzes the test results through artificial intelligence and computer algorithms. It can output diagnostic results with high sensitivity and specificity for clinical tests. Acute kidney injury (AKI) is a common clinical emergency. The main clinical features are elevated blood creatinine, decreased urine output, and sharp decline in renal function within a short period of time, and it is a hot spot worldwide. In this experiment, a rabbit sepsis model was replicated by inoculating E. coli bacteria into the rabbit's unilateral ureteral lumen and ligation. NaHS was used as an exogenous hydrogen sulfide donor to observe the effects of hydrogen sulfide on UTIs. The protective effect of oxidative stress and inflammatory response in acute kidney injury with hyperemia. In the experiment, the production of endogenous hydrogen sulfide was decreased in the Sepsis group, and the renal CSE activity was decreased, while the content of endogenous hydrogen sulfide in the NaHS group was higher than that of the Sepsis group, and the CSE activity of renal tissue was increased. It can be seen that the plasma hydrogen sulfide and renal tissue SCE levels in septic acute kidney injury increased after NaHS intervention, and the renal tissue damage was reduced, suggesting that hydrogen sulfide is mainly generated endogenously through the action of CSE, which causes damage to the kidneys. The expressions of iNOS and HO-1 in renal tissues of urinary sepsis are increased. H2S can play a certain protective effect on acute kidney injury in urinary sepsis by down-regulating iNOS and up-regulating the expression of HO-1.